2023
DOI: 10.1177/00469580231189601
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Fat Intake, and Body Mass Index in Health Professionals Working in a Public Hospital: A Cross-Sectional Study

Cristabel Vasquez-Purí,
Jhoes Naylin R. Plaza-Ccuno,
Anderson N. Soriano-Moreno
et al.

Abstract: Burnout can have a negative influence on dietary intake, promoting unhealthy eating behaviors in health care workers. This study determined the association between burnout, saturated fat intake, and body mass index (BMI) in a group of health care workers. A cross-sectional study was conducted in 300 health professionals residing in Rioja, Department of San Martin, Peru. Data were collected through an online and face-to-face survey. Burnout was assessed using a scale adapted and validated in the Peruvian popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Bahlaq et al found that the BMI levels of dental and medical students were associated with burnout [ 35 ]. Vasquez-Purí et al reported that BMI had no effect on the burnout levels of health professionals working in public hospitals [ 36 ]. This study found that the BMI of dentists was not associated with burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Bahlaq et al found that the BMI levels of dental and medical students were associated with burnout [ 35 ]. Vasquez-Purí et al reported that BMI had no effect on the burnout levels of health professionals working in public hospitals [ 36 ]. This study found that the BMI of dentists was not associated with burnout.…”
Section: Discussionmentioning
confidence: 99%
“…A healthy population of nursing personnel represents a primary issue in public health. Several researchers have highlighted the great incidence of overweight and obesity among nurses [ 1 ], and others have analyzed the quality of nurses’ eating habits and their related physical activity levels [ 2 ]. However, few studies have described how nurses might not be empowering in health-promoting self-care.…”
Section: Introductionmentioning
confidence: 99%
“…Culturally, women also assume caregiver roles in the home, in the family, and in the community, which often overlaps with the workload and less personal investment [ 27 ], being associated with lower psychological well-being when compared to males [ 26 ]. Vasquez-Purí et al [ 28 ] stress that women may report lower psychological well-being, which may be associated with accumulation in their role as mothers and have a higher burden inherent to the care of the home and children, which often adds to the demands of the work context.…”
Section: Introductionmentioning
confidence: 99%